Education of Friends as Improves Knowledge and Attitudes of Youth Adolescents - Andriyan, Aric Frendi; Murni, Arina Widya; Fatmadona, Rika (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Early detection is the first step in breast cancer prevention which targets can be done during adolescence, early detection in adolescents needs to be done through peer educators because adolescents prefer information from peers rather than parents or teachers, so that the material presented can improve BSE knowledge and attitude. This study aims to determine the effect of peer health education regarding knowledge and attitudes of BSE. The research design used a quasi-experimental study with a pre-post approach with a control group. Young women are the population in this study, with the sampling technique using purposive sampling. The sample used was 240 female teenage respondents according to the inclusion and exclusion criteria. Data collection using a questionnaire with Cronbach's alpha is 0.941> 0.7 for knowledge and 0.890 (> 0.361) for attitudes. Data analysis using the Wilcoxon test. The results showed that there was a difference between the pre-test median knowledge score was 14 and increased to 22 after the post-test with a P value of  0.000 <0.05 and the pre-test attitude median value was 17 increasing to 23 after the post-test with P Value 0.000 <0.05. Based on the research, it can be concluded that peers are very influential in increasing BSE knowledge and attitudes so that it is very important in early detection of breast cancer.